The Influence Of Brand Image, Relationships Marketing, Celebrity Endorses, On Dedicions To Purhase Halal Cosmetic Products Online In The Market Place - sabrina, rina nur; Antoni, syafrul syafrul (Jurnal Ilmiah Ekonomi Islam, 2024)
In the realm of societal needs, cosmetics, particularly for enthusiasts who prioritize halal products, emerge as essential commodities. Within the halal cosmetics business, understanding market demand becomes pivotal, requiring a comprehensive grasp of the factors influencing online purchasing decisions. This research, conducted in Sungai Banyak, seeks to unravel the elements influencing the online purchase of halal cosmetics in the marketplace, anchored in demand theory. The selected factors include Brand Image (X1), Relationship Marketing (X2), and Celebrity Endorsement (X3). Utilizing quantitative methods and processing data through the SPSS 25 application, the study involved 75 respondents, aligning with the substantial interest and usage of cosmetics in Sungai penuh. The research findings consistently reveal that Brand Image, Relationship Marketing, and Celebrity Endorsements all exert Keywords : Band Image, Relationship Marketing, Celebrity Endorse, halal kosmetic produc, market place